Self-assembling of fibers inside an injectable calcium phosphate bone cement: a feasibility study. (June 2022) - Di Filippo, M.F.; Giuri, D.; Marchiori, G.; Maglio, M.; Pagani, S.; Fini, M.; Tomasini, C.; Panzavolta, S.
Abstract: Calcium phosphate cements are biocompatible, bioactive, and osteogenic systems which have the potential to mimic the mineral phase of native bone and the ability to be molded into bone defects and implant sites, then harden in situ to provide stability. However, their mechanical strength needs to be improved. In the last few decades, the incorporation of preformed fibers into a brittle cement matrix has been proven to increase the mechanical properties. To obtain a better cohesion between the fibers and the cement paste thus improving the mechanical performances, in this work, we attempted the formation of self-assembling fibers in a single step during the setting of our calcium phosphate cement formulations. The formation of fibers was achieved by introducing a low-molecular-weight gelator (MW < 1000 Da) derived from l -Dopa: Boc-l -Dopa (Bn)2 -OH. This molecule can form supramolecular structures, owing to weak interactions, and chelate Ca 2+ ions to arrange into a fibrous network. The morphological analysis revealed that the gel was able to form fibers even inside such a dense matrix and their presence provided mechanical reinforcement both when tested in compression and in bending. Micro-CT analyses showed no variation in the total porosity, but an increase of pores diameter was observed when fibers are present. Moreover, the reinforced cements were able to ensure good cell viability and to express the main gene markers that are necessary for bone formation. Graphical abstract: Image 1 Highlights: Boc-L-Dopa (Bn)2-OH able to arrange into fibrous network in gel state was employed. Fibers successfully self-assemble even inside the matrix during cement hardening. A good dispersion and interfacial adhesion between fibers and cement was achieved. A significant improvement of mechanical properties was obtained.